Manfaat Corporate Social Responsibility Pada Perusahaan dan Masyarakat - Diva Mahes Wari; Cahyani, Rusnandari Retno (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2025)
This study aims to examine the impact of Corporate Social Responsibility (CSR) based on social entrepreneurship on both companies and communities, with a focus on community empowerment and social well-being improvement. Using a qualitative approach with a literature review method, this research analyzes various literatures related to CSR, social entrepreneurship, and its impact on local economic empowerment. The results indicate that CSR based on social entrepreneurship provides long-term benefits for both companies and communities. Companies that implement CSR with a social entrepreneurship approach can enhance their reputation, strengthen customer loyalty, and create mutually beneficial collaborations with local communities. For communities, this type of CSR opens up job opportunities, enhances entrepreneurial skills, and reduces dependence on social assistance. However, the main challenge in CSR implementation in remote areas is the limited infrastructure, access to education, and resources. This study also provides important implications for companies, governments, and communities in optimizing the sustainability of CSR programs based on social entrepreneurship. It is hoped that this research will serve as a reference in developing more sustainable CSR strategies, particularly in areas that require further economic empowerment.